Aprovechamiento de los residuos de la producción del durazno en Colombia (2022)
There are different varieties of peach (Prunus persica) in Colombia, which are grown at altitudes between 1,400 and 2,600 meters above sea level. For 2019, the production in Colombia was 30,038 tons of peach according to the National Agricultural Survey (ENA) of the year 2019, where the main production was found in the department of Santander with 37.76%, followed by the departments of Norte de Santander with 33.55%, Boyacá with 24.14%, Cundinamarca with 2.38%, Huila with 2.13% and Tolima with 0.27%. For 2020, according to the Food and Agriculture Organization of the United Nations (FAO), the production was 32,985 tons. The weight of the fruit varies between 100 and 160 g, of which approximately between 88% and 92% corresponds to the pulp (mesocarp); therefore, in 2019 there were more than 2,403 tons of peach waste and in 2020 more than 2,638 tons.